To determine the relationship between dietary intake, body composition and incidence of upper respiratory tract infections in triathletes during training and competition for the Ironman - Main, Carey Anne (Stellenbosch : Stellenbosch University, 2013)
Thesis (MNutr)--Stellenbosch University, 2013.